Pengaruh Pemberian Reward Dan Promosi Jabatan Terhadap Prestasi Kerja Melalui Semangat Kerja Sebagai Varibel Intervening Pada Karyawan Pt Telkom Witel Riau Daratan Pekanbaru - Hutabarat, Helen Natalia; Suryalena, Suryalena (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This research aims to determine the direct effect of giving Rewards and promotions on work performance through work enthusiasm as an Intervening variable in employees of PT Telkom Witel Riau Daratan Pekanbaru. The method used in this research is descriptive quantitative analysis using the Smarpls application program. The population in this study was 52 permanent employees of PT Telkom Witel Riau Daratan Pekanbaru. The results of this study show that Rewards do not have a direct effect on work performance, there is a direct effect of giving Rewards on work morale significantly, there is a direct effect of job promotion on work performance significantly, there is also a direct effect of job promotion on work morale, and finally there is a direct effect Work spirit has a significant impact on work performance among employees of PT Telkom Witel Riau Daratan Pekanbaru.